2015
DOI: 10.1016/j.tvjl.2015.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for neonatal calf diarrhoea and enteropathogen shedding in New Zealand dairy farms

Abstract: To investigate the risk factors for neonatal calf diarrhoea, a cross-sectional study was conducted on 97 New Zealand dairy farms. Faecal specimens from 1283 calves were scored as liquid, semi-solid or solid, and analysed for bovine rotavirus (BRV) and coronavirus (BCV), enterotoxigenic K99(+)Escherichia coli (K99), Salmonella spp. and Cryptosporidium parvum. Calf- and farm-level data were collected by means of a questionnaire and the odds of liquid faeces calculated using mixed effects logistic regression mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
63
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(85 citation statements)
references
References 29 publications
(40 reference statements)
13
63
1
3
Order By: Relevance
“…Among them, Cryptosporidium spp. and rotavirus are most frequently identified in fecal specimens from neonatal calves all over the world (Cho et al, 2013;Al Mawly et al, 2015;Mohamed et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, Cryptosporidium spp. and rotavirus are most frequently identified in fecal specimens from neonatal calves all over the world (Cho et al, 2013;Al Mawly et al, 2015;Mohamed et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that detection of rotavirus in the presence of diarrhea is a significant finding in calf diarrhea (Cho et al, 2013). Additionally, rotavirus has been shown to be significantly associated with liquid diarrhea in 9-to 21-day-old dairy calves (Al Mawly et al, 2015) and also in beef calves (Cho et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that the presence of RVA infection in feces from diarrheic calves is significantly higher than that in nondiarrheic feces (Al Mawly et al, 2015;Bartels et al, 2010;Chitambar et al, 2011). Forty-eight of the 357 (13.4%) diarrheic fecal samples evaluated were RVA-positive.…”
Section: Resultsmentioning
confidence: 88%